Analysing Factors Improving Business Models of Fruit Parcel Enterprise in Jepara Central Javaâ€“Case Study Putra Karya Indah Parcel - Dimas Bagus Wiranatakusuma; Nur Marina Binti Abdul Manap (Jurnal Kewarganegaraan, 2022)
AbstractBackground: â€œPutra Karya Indahâ€ parcel is one of small enterprises in Jepara which has many years run the business in fruit parcel sector. Traditional managerial method is of among the crucial factors which makes the business development slowly increases. Hence, the program is created to observe. Method: This program was conducted through direct observation to Putra Karya Indahâ€™s enterprise and literature analysis on how to improve the performance of the Putra Karya Indah, in particular, and other small enterprises (SE) in general. Result: According to the literature analysis, the main problem faced by SE is the dynamic capabilities among manager and leader who manage the enterprises. Therefore, to settle such problems, a resilient employee is need in the sense that they can balance between innovation and sustainability issue altogether. Conclusion: Putra Karya Parcel is a promising enterprise given long experience has been taking place over the years. However, business transformation either in the form of human management and business process need to be undertaken for ensuring the sustainability in the long run.Keywords: Business Models, Fruit Parcel Enterprise, Jepara